Potential role of tenofovir vaginal gel for reduction of risk of herpes simplex virus in females - Tan DHS (Dove Medical Press, 2012)
DHS TanDivisions of Infectious Diseases, St Michael's Hospital, University Health Network, and University of Toronto, Toronto, CanadaAbstract: A surprising result of the groundbreaking CAPRISA-004 trial, which demonstrated the efficacy of vaginal tenofovir 1% gel in reducing the risk of human immunodeficiency virus (HIV)-1 infection by 39% in heterosexual women, was the added benefit of this microbicide in reducing acquisition of herpes simplex virus type 2 (HSV-2) by 51%. HSV-2 is the most common cause of genital ulcer disease worldwide, and is responsible for considerable morbidity among women and neonates. The virus is further implicated in increasing the risk of both HIV acquisition and transmission, and may have additional adverse consequences in HIV-coinfected persons, making HSV-2 prevention an important clinical and public health objective. While tenofovir had not previously been widely considered to be an anti-herpes drug, in vitro activity against HSV is well documented, raising interest in potential future applications of tenofovir and its prodrugs in HSV-2 control. This article reviews the currently available data for tenofovir as an anti-herpes agent, as well as unanswered questions about delivery systems, drug formulation, rectal administration, drug resistance, and clinical applications.Keywords: tenofovir, herpes simplex virus type 2, microbicide, CAPRISA-004